Sistem Informas Manajemen Laporan Keuangan Majelis Taklim Jami’ Nurul Hasanah - Asep Sumantri; Khaerul Anam; Niken Harsanti; Sekar Ageng Pratiwi; Zaskia Ananda Fahra; Nazwa Dwi Rahmawati (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2025)
Based on Law Number 20 of 2003 concerning the National Education System, the Majelis Taklim is included in the category of non-formal educational institutions as regulated in Article 106. This institution has a strategic role in fostering and developing the lives of the community to be more pious to Allah SWT. The Majelis Taklim functions as a forum that supports the formation of active and constructive community characters. At the Jami' Nurul Hasanah Mosque, the da'wah activities carried out are often supported by the Majelis Taklim cash funds, which are used for various social needs such as cleaning fees, lighting costs and infrastructure repairs, as well as compensation funds for residents who experience disasters such as illness or death. When the mosque receives a grant from the Kelurahan or other agencies, management and reporting of these funds becomes a must. However, the recording system currently used is still manual with a ledger, so it does not support effective and efficient management. With the financial management information system, the Majelis Taklim management can more easily and accurately manage cash and prepare financial reports for the Jami' Nurul Hasanah Mosque. This solution supports the principle of good governance and realizes transparency in financial management.